Control and prevention of nosocomial infection - Reddy, Palle Lokhnah; Chand, Aluka Anand (International Journal Of Community Medicine And Public Health, 2020)
Background: The center for disease control and prevention estimates that 1.5 million people suffer from hospital acquired infection every year and hereby one lack people die. Major nosocomial infections (NIs) are ventilator associated pneumonia (VAP), urinary tract infection (UTI), surgical site infection (SSI) and blood stream infections (BSI). Methods: This was a retrospective multicenter descriptive study involving 2000 consecutive patients in ICU for a period of 2 years. The data was compared with the data available from National Nosocomial infection surveillance. NIs were analyzed by infection site and pathogen distribution. Results: The main factors responsible for NI are both hospital and patients. Almost 40% UTI’s contribute to NI’s, 30% VAP’s, 20% SSI and 10% BSI respectively. Nosocomial infections can be reduced by better surveillance system and infection control. Primary blood stream infections, pneumonia and UTI associated with invasive devises made up the great majority of nosocomial infections. Conclusion: We can reduce NI’s by proper use and care of urine catheters, proper use and care of vascular accesses lines, by proper surveillance of surgical procedure and by proper hand and hygiene standard precautions.